2006
DOI: 10.5551/jat.13.216
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Atherosclerotic Effects of Lipid Lowering with Atorvastatin in Patients with Hypercholesterolemia

Abstract: We investigated the lipid lowering and anti-atherosclerotic effects of atorvastatin in patients with hypercholesterolemia. Thirty patients were given atorvastatin 10 mg daily, and assessed for serum lipids, intima-media thickness (IMT), and brachial-ankle pulse wave velocity (ba-PWV) at the baseline, 6 months, and 12 months. Remnant-like particle-cholesterol (RLP-C), lipoprotein (a) (Lp(a)), and high-sensitivity C-reactive protein (hs-CRP) were measured in some patients at the baseline and at 6 months. Total c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
4
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 22 publications
1
36
4
1
Order By: Relevance
“…Vascular calcification and increased arterial stiffness are associated with reduced baroreflex sensitivity, potentially producing short-term dysregulation of blood pressure 26) . Although, in our study, treatment with ARBs or statins was not associated with improvement in the severity of arterial stiffness in non-diabetic CKD patients, recent studies have found that longterm blockade of the renin-angiotensin system might prevent increased arterial stiffness and vascular calcification and thereby reduce the incidence of cardiovascular events [27][28][29] . Thus, evaluation of the effects of treatment with ARBs or statins should include a longer follow-up period for precise determination of the significance of arterial stiffness and vascular calcification.…”
Section: Discussionmentioning
confidence: 45%
“…Vascular calcification and increased arterial stiffness are associated with reduced baroreflex sensitivity, potentially producing short-term dysregulation of blood pressure 26) . Although, in our study, treatment with ARBs or statins was not associated with improvement in the severity of arterial stiffness in non-diabetic CKD patients, recent studies have found that longterm blockade of the renin-angiotensin system might prevent increased arterial stiffness and vascular calcification and thereby reduce the incidence of cardiovascular events [27][28][29] . Thus, evaluation of the effects of treatment with ARBs or statins should include a longer follow-up period for precise determination of the significance of arterial stiffness and vascular calcification.…”
Section: Discussionmentioning
confidence: 45%
“…Yokoyama et al showed that fluvastatin treatment at 40 mg daily for 12 months produced a significant decrease of PWV 19) . On the other hand, Ozaki et al reported that atorvastatin treatment at 10 mg daily significantly reduced hsCRP at 6 months, but had no significant effect on baPWV 20) . A comparative study among pravastatin, simvastatin and fluvastatin showed that although serum hsCRP levels decreased significantly in all three statin groups, the effects on PWV differed among the three drugs after a 12-month treatment period: PWV showed no change in the pravastatin group, was transiently reduced in the simvastatin group, and was significantly decreased in the fluvastatin group 21) .…”
Section: Discussionmentioning
confidence: 99%
“…Women with surgical menopause (bilateral oophorectomy), hormone replacement therapy, thyroid disorders, digitalis and corticoid intake, autoimmune or systemic disease, gonadal disorder, polycystic ovary syndrome (PCOS), active malign process, recent (!1 month) severe infection, and recent (!1 month) stroke were excluded. Women taking lipidlowering agents or antihypertensives that might have an influence on the arterial intima media thickness (IMT) were not excluded because the extremely limited decrease of IMT observed in several studies (13,14) did not significantly influence the grade of ICA stenosis.…”
Section: Patientsmentioning
confidence: 99%